Identification of sensitive raw materials at a milk preparation room of a neonatal intensive care unit in the Canselor Tuanku Muhriz Hospital - Mahirah Mohamad,; Shareena Ishak,; Norrakiah Abdullah Sani, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The implementation of a Hazard Analysis and Critical Control Point (HACCP) system in infant milk preparation can prevent and reduce the risk of bacterial contamination in infant feedings. Therefore, it is very important to determine the sensitive raw materials (SRM) in a milk room of a neonatal intensive care unit (NICU) to prevent contamination that can affect the safety of milk feeding. This study was conducted to identify the SRM at the milk preparation room of a NICU in the Canselor Tuanku Muhriz Hospital, Cheras, Kuala Lumpur, Malaysia. SRM were identified via HACCP system decision tree by the Malaysian Standard (MS1480:2007). The results showed that donor expressed breast milk (DEBM), expressed breast milk at home (EBMH), freshly expressed breast milk (FEBM) and powdered infant formula (PIF) were identified as SRM. Expressed breast milk (DEBM, EBMH, FEBM) were known as non-sterile milk which were able to transmit pathogenic microorganisms such as Klebsiella pneumoniae and Pseudomonas aeruginosa derived from the mother or donor. PIF is also not sterile that are associated with Cronobacter sakazakii and Salmonella infections causing serious illnesses among premature and infants. Ready to feed milk (RTF) is classified as non-sensitive material as it is sterile, free from bacterial contamination and safe for high-risk infant’s feeding compare to PIF. Preventive measures were applied to control the significant hazards in all identified SRM to ensure the final product (milk) is safe for consumption.